2006
DOI: 10.1371/journal.pone.0000093
|View full text |Cite
|
Sign up to set email alerts
|

Wnt and Hedgehog Are Critical Mediators of Cigarette Smoke-Induced Lung Cancer

Abstract: BackgroundLung cancer is the leading cause of cancer death in the world, and greater than 90% of lung cancers are cigarette smoke-related. Current treatment options are inadequate, because the molecular basis of cigarette-induced lung cancer is poorly understood.Methodology/Principal FindingsHere, we show that human primary or immortalized bronchial epithelial cells exposed to cigarette smoke for eight days in culture rapidly proliferate, show anchorage-independent growth, and form tumors in nude mice. Using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
102
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(105 citation statements)
references
References 29 publications
2
102
0
1
Order By: Relevance
“…Accordingly, in preliminary studies using SYBR Green-based quantitative PCR, we found that CS upregulated two established nuclear targets of Wnt/␤-catenin/Lef-1 signaling pathway, WISP1 (WNT1 inducible signaling pathway protein1, 5.86-fold-increase) and FGF4 (fibroblast growth factor 4, 19.45-fold-increase) (unpublished data). 35,36 Although the activation of canonical Wnt signaling has been reported in previous publications using HBE cell monolayers, 10,23 to the best of our knowledge this study is the first to demonstrate CS-induced activation of Wnt signaling in a fully differentiated pseudostratified model of the human airway epithelium that compromises three heterogeneous cell populations (ciliated columnar cells, goblet cells, and undifferentiated basal cells). Moreover, we established a pathological link between upstream EGFR and downstream canonical Wnt signaling in response to CS exposure.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Accordingly, in preliminary studies using SYBR Green-based quantitative PCR, we found that CS upregulated two established nuclear targets of Wnt/␤-catenin/Lef-1 signaling pathway, WISP1 (WNT1 inducible signaling pathway protein1, 5.86-fold-increase) and FGF4 (fibroblast growth factor 4, 19.45-fold-increase) (unpublished data). 35,36 Although the activation of canonical Wnt signaling has been reported in previous publications using HBE cell monolayers, 10,23 to the best of our knowledge this study is the first to demonstrate CS-induced activation of Wnt signaling in a fully differentiated pseudostratified model of the human airway epithelium that compromises three heterogeneous cell populations (ciliated columnar cells, goblet cells, and undifferentiated basal cells). Moreover, we established a pathological link between upstream EGFR and downstream canonical Wnt signaling in response to CS exposure.…”
Section: Discussionmentioning
confidence: 66%
“…18 -20 Moreover, in company with the redistribution of EGFR and ␤-catenin, short-term exposure of HBE cell monolayers to CS has been shown to initiate signaling events that include aberrant activation of both EGFR and canonical Wnt/␤-catenin signaling. [21][22][23] While EGFR and Wnt are known mediators of CS-induced airway diseases, the specific events that coordinate cytoarchitectural damage and aberrant activation of protumor signaling are unclear.…”
mentioning
confidence: 99%
“…In mice, approximately 20 days of treatment with cyclopamine are sufficient to abolish the tumors and prevent recurrence and metastasis [48], suggesting that limited treatments will be efficacious. Finally, the finding that oncogenic RAS requires positive GLI activity in several contexts [48] and that HH-GLI is also activated by other cancer-inducing agents, such as tobacco smoke [82], suggests that the GLI code participates in a vast number of human cancers. The dependence of many human tumors on high positive GLI activity thus represents an unexpected common target.…”
Section: Discussionmentioning
confidence: 99%
“…The Wnt pathway has been associated with normal lung development and homeostasis as well as chronic lung diseases such as fibrosis and asthma (Konigshoff et al, 2010;Van et al, 2008). However, there are contradictory findings indicating that the Wnt pathway is activated or down-regulated by cigarette smoke in bronchial epithelial cells (Lemjabbar-Alaoui et al, 2006;Wang et al, 2011). Wnt inhibitory factor 1 (Wif1), an extracellular antagonist that acts by binding to Wnt ligands, is a frequent target for epigenetic silencing in various human cancers (Ying et al, 2009).…”
Section: Introductionmentioning
confidence: 99%